Stepwise Sironko visual walk through - Margiotta, S. (International Institute of Tropical Agriculture, 2019)
The video walks the viewer through a Stepwise Sironko pilot site in a smallholder farmer field, capturing visual reference to each step of the Stepwise approach, highlighting conditions of the coffee in each step, and the incremental value of each set of practices applied by the farmer as part of the Stepwise approach being piloted.